Operations research techniques for capital investments - Hanssmann, Fred. (New York : John Wiley & Sons, Inc., 1968)
This book deals with the application of operations research methodology to capital investment decisions. This book has case examples from all these areas like plant and physical assets, markets and research development and exploration.
Including bibliographical references
osa 9/4/19
Loans
Keywords: Capital investments; Mathematical models; Operations research